Pengaruh Sistem Informasi Akuntansi dan Teknologi Informasi Pada Kinerja Keuangan - Paramita, Dian; Zahara, Inna (Akuisisi : Jurnal Akuntansi, 2025)
Accounting information system and information technology cannot be ignored in the preparation of SME financial reports which are needed for internal and external purposes. This research aims to analyze the influence of accounting information systems and information technology on financial performance in Small and Medium Enterprises (UKM) in Sleman Regency, as well as the moderating role of financial literacy in the relationship between accounting information systems and information technology. As a sampling method, this research uses a purposive sampling technique. The number of samples used was 61 respondents who were registered with the Sleman Regency Cooperatives and Small Business Service and had complete company profiles for research purposes. Data was collected through questionnaires. Data analysis in this research was carried out using the SEM-PLS (Partial Least Square) method. The research results show that accounting information systems and information technology have a positive and significant influence on financial performance. In addition, financial literacy acts as a moderator in the impact of accounting information systems and information technology on financial performance.